Digital financial transformation: An Islamic economic analysis of online lending in the era of industrial revolution 4.0 - Marta, Dwi Jati; Utami, Atikah Dewi (Journal of Islamic Law on Digital Economy and Business, 2025)
Purpose – This study critically examines online lending practices by evaluating their compliance with Sharia principles. The research also highlights the interplay between regulations, public digital-financial literacy, and Sharia-based fintech innovation, and proposes a digital business model that is fair, transparent, and sustainable. Methodology – This research uses a descriptive qualitative literature review by systematically analyzing primary and secondary sources. This analysis followed systematic review guidelines through the stages of selection, data reduction, thematic analysis, and contextual interpretation, ensuring validity, timeliness, and relevance in synthesizing theory and empirical findings. Findings – This research shows that although digital transformation in the financial sector, particularly online lending, brings efficiency and wider access, it also raises serious issues regarding Sharia compliance. By integrating regulatory perspectives, digital-financial literacy, and Sharia financial technology, this study research reveals a gap between Islamic principles, such as the prohibition of usury, uncertainty, and exploitation, and the reality of online lending practices. Implications – This study highlights the urgent need for stricter regulations to protect consumers and ensure Sharia compliance in online lending. The Islamic fintech sector emphasizes the importance of developing business models based on justice and sustainability, utilizing alternative contracts, such as mudharabah and musyarakah. Originality – This research contributes to originality by integrating multidimensional perspectives—regulation, literacy, and Sharia-driven fintech innovation—offering a more holistic view than prior studies. It also reinforces the relevance of maqāṣid al-sharīʿah as both a normative and a practical foundation for ethical and inclusive fintech governance.